Endothelin-1 as a Candidate Biomarker of Systemic Sclerosis: A GRADE-Assessed Systematic Review and Meta-Analysis With Meta-Regression - Arduino A Mangoni; Angelo Zinellu (Biomarker Insights, 2025)
Background: There is an ongoing search for novel biomarkers of vascular dysfunction, extent of fibrosis and organ involvement in systemic sclerosis (SSc). Objectives: We critically appraised the studies investigating the circulating concentrations of endothelin-1 in SSc patients and healthy controls. Design: This was a systematic review with meta-analysis. Data sources and methods: We searched electronic databases (PubMed, Scopus, and Web of Science) from inception to 15 June 2024. We assessed the risk of bias and the certainty of evidence using the JBI Critical Appraisal Checklist and GRADE, respectively. Results: Endothelin-1 concentrations were significantly higher in SSc patients than in controls (26 studies; standardised mean difference, SMD = 0.98, 95% CI 0.73-1.23, P  < .001; moderate certainty of evidence). In SSc patients, there were no significant differences in endothelin-1 concentrations between those with limited and diffuse cutaneous SSc (10 studies; SMD = 0.32, 95% CI −0.07 to 0.71 P  = .11; very low certainty), and with and without digital ulcers (5 studies; SMD = 0.82, 95% CI −0.06 to 1.69, P  = .066; very low certainty), pulmonary arterial hypertension (7 studies; SMD = 0.22, 95% CI −0.01 to 0.45, P  = .066; very low certainty) or interstitial lung disease (3 studies; SMD = 0.09, 95% CI −0.18 to 0.35, P  = .51; very low certainty). There was limited evidence in SSc patients with different video capillaroscopy pattern and telangiectasias. Subgroup and meta-regression analyses showed significant associations between the effect size and geographical location (studies investigating SSc patients and controls), year of publication (studies investigating SSc patients with limited and diffuse cutaneous SSc), and biological matrix assessed (studies investigating SSc patients with and without digital ulcers). Conclusion: The results of this systematic review and meta-analysis highlight the potential role of endothelin-1 as a candidate biomarker of SSc. Further research is warranted to determine the utility of measuring endothelin-1 in SSc subgroups with different extent of fibrosis and organ involvement. Registration: PROSPERO registration number - CRD42024566461.